Literature review on the use of action research in higher education. Issue 1 (1st January 2017) - Gibbs, Paul; Cartney, Patricia; Wilkinson, Kate; Parkinson, John; Cunningham, Sheila; James-Reynolds, Carl; Zoubir, Tarek; Brown, Venetia; Barter, Phil; Sumner, Pauline; MacDonald, Angus; Dayananda, Asanka; et al.
Abstract: This literature review considers the use of action research in higher education. The review specifically looks at two areas of higher education activity. The first concerns academic teaching practice and includes a discussion of research and pedagogy practice, and staff development. The second considers student engagement. In both of these core features of higher education, action research has proven to be a central approach to the investigation, reflection and improvement of practice. Each of these main foci includes a discussion of the limitations of the literature. The review illustrates the extent and range of uses to have benefited from an action research approach.